1983
DOI: 10.1002/eji.1830130814
|View full text |Cite
|
Sign up to set email alerts
|

Biological and biochemical characterization of an interleukin 1‐like factor from rat C6 glioma cells

Abstract: It has been previously reported that lipopolysaccharide-stimulated murine astrocytes produce a factor which enhances the proliferative response of thymocytes to lectins. The present report demonstrates that a rat astrocytoma cell (C6 cells)-derived factor appears to be similar to macrophage-derived interleukin 1 (IL 1) in its biological activities and biochemical characteristics. Upon injection into mice, supernatants of C6 cells induce the production of serum amyloid A. The C6 cell-derived factors enhance the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(45 citation statements)
references
References 16 publications
1
44
0
Order By: Relevance
“…The vacuolation of myelinated axons in experimental CJD (2), scrapie (3, 4), and kuru (5) closely resembles that induced by tumor necrosis factor a (TNF-a) in murine spinal cord organotypic cultures (6) and that found in demyelinating diseases, such as experimental allergic encephalitis (EAE) (7-11) and multiple sclerosis (MS) (12, 13). Moreover, our recent studies indicate similar pathological lesions in the optic nerves of mice after intraocular inoculation with recombinant murine TNF-a (14).TNF-a and interleukin la (IL-la) are synthesized in microglia and astrocytes (15)(16)(17)(18)(19)(20), and immunopositivity for these cytokines has been detected in neurons (20 …”
mentioning
confidence: 84%
See 1 more Smart Citation
“…The vacuolation of myelinated axons in experimental CJD (2), scrapie (3, 4), and kuru (5) closely resembles that induced by tumor necrosis factor a (TNF-a) in murine spinal cord organotypic cultures (6) and that found in demyelinating diseases, such as experimental allergic encephalitis (EAE) (7-11) and multiple sclerosis (MS) (12, 13). Moreover, our recent studies indicate similar pathological lesions in the optic nerves of mice after intraocular inoculation with recombinant murine TNF-a (14).TNF-a and interleukin la (IL-la) are synthesized in microglia and astrocytes (15)(16)(17)(18)(19)(20), and immunopositivity for these cytokines has been detected in neurons (20 …”
mentioning
confidence: 84%
“…TNF-a and interleukin la (IL-la) are synthesized in microglia and astrocytes (15)(16)(17)(18)(19)(20), and immunopositivity for these cytokines has been detected in neurons (20 …”
Section: Introductionmentioning
confidence: 99%
“…Genomic sequencing has recognized more than 90 deubiquitinylating cysteine protease enzymes (Fontana et al, 1982). Deubiquitinylating enzymes (DUBs) play roles in Ub recycling, can reverse Ub, and edit inappropriately ubiquitinylated proteins.…”
Section: Ubiquitinmentioning
confidence: 99%
“…Families of Ub-like molecules (Ubl) are being discovered that act antagonistically to, or independently of, Ub to control the fate and function of proteins (Yeh et al, 2000). A plethora of deubiquitinylating enzymes (Fontana et al, 1982) have been identified that must play key roles in moderating and reversing Ub, although their physiological functions are still largely unknown (Chung and Baek, 1999;Wilkinson, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…rIL-la (1 fM to 1 ,uM) induced a 150% increase in iCRH secretion over baseline from F344/N hypothalami (P < 0.001, ANOVA) and a 10%o increase in iCRH secretion over baseline from LEW/N hypothalami (not significant, ANOVA). Bacterial endotoxin (lipopolysaccharide, similar to SCW) and IL-1 have been shown to augment levels ofCRH, ACTH, and corticosterone through stimulation of the HPA axis at multiple levels (35)(36)(37)(38)(39)(40)(41)(42)(43)(44). Since SCW induces IL-1 release (45), IL-1 is one probable mediator of SCW-induced HPA-axis stimulation.…”
mentioning
confidence: 99%